Nontuberculosis mycobacteria (NTM) infections in patients with leukemia: a single center case series - Marvin-Peek, Jennifer; Sasaki, Koji; Kontoyiannis, Dimitrios P.; Adachi, Javier; Ohanian, Maro; Takahashi, Koichi; Issa, Ghayas C.; Kornblau, Steven; Abbas, Hussein A. (Frontiers in Medicine, 2024)
Patients with leukemia experience profound immunosuppression both from their underlying disease as well as chemotherapeutic treatment. Little is known about the prevalence and clinical presentation of nontuberculous mycobacteria (NTM) in this patient population. We identified six cases of NTM infection from 29,743 leukemia patients who had acid-fast bacilli (AFB) cultures. Four cases had bloodstream infections and five had disseminated disease, including one who presented with an unusual case of diffuse cellulitis/myositis. All patients were lymphopenic at time of diagnosis, and two patients ultimately died from their NTM infection. NTM infections are a rare, but potentially life-threatening infection in patients with leukemia. Sending AFB cultures early is important to direct appropriate antimicrobial therapy and allow for future leukemia-directed therapy.